Wybrane aspekty controllingu logistycznego w obszarze produkcji - Biadacz, Renata (Chosen aspects of logistic controllership in the production area, 2006)
Supporting the function of logistic management becomes the necessity at present, especially when one takes into consideration the increasing complexity of logistic decision process, irrrespect of both enlarged supply of decision problem information and more complicated methods and instruments of management. The use of logistic controllership may be functional. The aim of the paper is to present the essence of logistic controllership and to point out the role it plays in the production area. The study does not write the problem fully out.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 37-42